Administrators' Perceptions of School-Based Management - Stephen L. Jacobson; Beth E. Woodworth (Educational Considerations, 1992)
The findings of this study suggest that the compatibility between the vision and reality of SBM in small rural districts make these sites ideal candidates for further analysis of the dynamics of increased school site autonomy.